Quantificação de fenóis, flavonoides totais e atividades farmacológicas de geoprópolis produzida pela abelha Plebeia aff. flavocincta no semiárido do Rio Grande do Norte - Silva, Jardel Bezerra da (2016)
The study aimed to evaluate the geopropolis bees Plebeia aff. flavocincta produced in Rio Grande Norte- Brazil, through the study of pharmacological activities, sensory characteristics and physical and chemical requirements. Investigated the antioxidant activity by the DPPH (2,2-diphenyl-1-picryl-hydrazyl), antibacterial, through the method of diffusion in agar and healing activity, by inducing experimental surgical wounds Rattus norvegicus in Berkenhout, 1769 Wistar. Quantified if the contents of total phenols and flavonoids through the Waterman and Mole methods, Woisky and Salatino, respectively. Samples of geopropolis showed consistency between the soft sticky resinous hard and hydroalcoholic extracts of geopropolis we identified 06 different types of scent, amber color, dark brown, green and colorless. The taste ranged from bitter to sweet and strong characteristic. All samples of the extracts showed up with liquid aspect, clear and smooth. The total phenolic content varied between 0,00 ± 0,00 and 9,4 ± 0,28% (m/m), the total flavonoid content of 0,0005 ± 0,0220 and 0,00003 ± 0,00037% (m/m). The antioxidant capacity of over 90% was observed in 05 samples. The extracts were found to be effective with respect to antimicrobial activity because of the 08 samples tested, 05 promoted inhibition zones ≥9mm front of all the strains tested. In wound healing assay of the experimental group, the base cream 20% geopropolis P. aff. flavocincta decreased the signs of inflammation and stimulate collagen production, accelerating the process of re-epithelialization, with no statistically significant difference in the areas of the wounds from the 9th day and complete healing on the 16th day. It follows that the geopropolis P. aff. flavocincta produced in semiarid RN, can be used as an alternative and natural principle in antibacterial activities, antioxidant and healing, characterized by a source of phenolic compounds